Spatial Diffusion of Leather Industries (Case Study at Magetan District) - Dilahur, Dilahur (Forum Geografi, 2002)
After the rise and the fall of the tides and the change of the activities as the phenomena which happen in the daily life of sociaety, the hange of spacing or distributionn of industrial businesses becomes one of the new phenomena. The objective of this research is to know the process of the diffusion from leather industry in Magetan Subdistrict. This research uses secondary data analysis and direct observation. The result of this research shows that the change (the rise and fall of the tides) in leather industry has producted the movement of distribution or spacing in which the center of the main production is declined and the new center may arise. In this movement, it seems that the existence of the specification on types of activity, like having similar leather, shoescraft, beltcraft, and sendalcraft become the serious phenomena. This kind of the change and its development is signed by the change of position from becoming employee to be new employer, having some employees that may become the employers at any time and so forth. The style of the diffusion which happen is the style of mixing diffusion in which the business on leather industry becomes wider reaching around the village while the original village (Kauman) is still as the center of industry, although it has so limited activities because the business is always declined.